Moving Imagination : Explorations of Gesture and Inner Movement - Preester, Helena De (Amsterdam : John Benjamins Publishing Company, 2013)
To know anything in space (for instance, a line), I must draw it, and thus synthetically bring into being a determinate combination of the given manifold, so that the unity of this act is at the same time the unity of consciousness (as in the concept of a line); and it is through this unity of consciousness that an object (a determinate space) is first known. Immanuel Kant, Critique of Pure Reason, B 138 (2007).
Prelim pages -- Table of contents -- Moving imagination -- Bodily resonance -- The moving body -- Movement, gesture, and meaning -- Achieved spontaneity and spectator's performative experience -- The motor dimension of the actor-spectator relationship -- The digital body in contemporary American cinema -- Embodiment -- Is gesture knowledge? A philosophical approach to the epistemology of musical gestures -- Sound in film as an inner movement -- Body English -- The somatic in kinetic sculpture -- Edgar Degas -- Time lines -- Styles of observation and embodiment -- Cy Twombly -- Pre-motor and motor activities in early medieval handwriting -- The neurophenomenology of gesture in the art of Henri Michaux -- Moving without moving -- The "I cannot, but it can" of aesthetic perception -- Name index -- Subject index
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Mind and body; Human beings -- Attitude and movement; Arts -- Psychological aspects; Arts audiences -- Psychology; Êtres humains -- Attitude et mouvement; Arts -- Aspect psychologique; Arts -- Publics -- Psychologie; ART -- Performance; ART -- Reference; Arts audiences -- Psychology; Arts -- Psychological aspects; Human beings -- Attitude and movement; Mind and body